Diffusive phosphorus fluxes in relation to the sediment phosphorus profile in Big Traverse Bay, Lake of the Woods. (2nd October 2017) - James, William F.
ABSTRACT: James WF. 2017. Diffusive phosphorus fluxes in relation to the sediment phosphorus profile in Big Traverse Bay, Lake of the Woods. Lake Reserv Manage. 33: 360–368. The role of sediment diffusive phosphorus (P) flux in the P economy and cyanobacteria blooms in Lake of the Woods (LOW) is needed to establish total maximum daily load requirements. I quantified aerobic and anaerobic diffusive P fluxes as a function of temperature to estimate annual internal P loading in Big Traverse Bay of LOW. Replicate cores were collected seasonally and incubated at 5, 11, 18, and 25 C for rate determination. In addition, a sediment core collected in February 2015 was sectioned to analyze sediment P fractions and characterize P burial. Aerobic and anaerobic diffusive P fluxes varied nonlinearly with temperature. Rates were lowest under aerobic conditions, ranging between 0.05 and 0.36 mg/m 2 /d, and much higher under anaerobic conditions, ranging between 0.77 and 16.78 mg/m 2 /d, at 5 and 25 C, respectively. The annual diffusive P flux contribution to Big Traverse was 38 and 1172 mg/m 2 /yr under aerobic and anaerobic conditions, respectively, based on mean monthly bottom temperatures in 2015. The sediment vertical P profile exhibited a distinct surface maximum, suggesting an imbalance between gross deposition and burial. Assuming a constant sedimentation rate, potential annual internal P loading was higher at 246 mg/m 2 /yr compared to the annual aerobic diffusive P flux, suggesting anaerobic diffusive P flux and other unmeasured internal P loading processes contributed to the P budget. Low P burial efficiency and maintenance of a surface P bulge may be due to cyanobacteria-mediated biological uptake of sediment P, recycling, and redeposition to the sediment surface.